2011
DOI: 10.3109/00016489.2011.576429
|View full text |Cite
|
Sign up to set email alerts
|

A single nasal dose of CCL20 chemokine induces dendritic cell recruitment and enhances nontypable Haemophilus influenzae-specific immune responses in the nasal mucosa

Abstract: Nasal application of CCL20 induced an increase in the number of dendritic cells in nasal-associated lymphoid tissue. P6-specific nasal wash immunoglobulin (Ig)A and serum IgG titers were elevated significantly after nasal immunization. Enhanced NTHi clearance from the nasopharynx was also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Chemokine production is important for the induction of mucosal immune responses following vaccination. Although many chemokines are associated with inflammatory responses, recent researches in the biological roles of chemokines such as CCL20 also allow to employ as potential vaccine adjuvants by regulating mucosal immune responses ( 16 , 43 ). Studies have shown that mucosal vaccination increases local chemokine production in the gut mucosa; these chemokines attract immune cells (including IgA-producing plasma cells) to the site of vaccination ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokine production is important for the induction of mucosal immune responses following vaccination. Although many chemokines are associated with inflammatory responses, recent researches in the biological roles of chemokines such as CCL20 also allow to employ as potential vaccine adjuvants by regulating mucosal immune responses ( 16 , 43 ). Studies have shown that mucosal vaccination increases local chemokine production in the gut mucosa; these chemokines attract immune cells (including IgA-producing plasma cells) to the site of vaccination ( 64 , 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCL20, also known as macrophage inflammatory protein-3α, binds to CC chemokine receptor-6 (CCR6) ( 12 ) and attracts immature DCs ( 13 ), memory T cells ( 14 ), and B cells ( 15 ). In addition, increased number of DCs induced by CCL20 upon mucosal vaccination is associated with the extent to which IgA and IgG levels in the nasal mucosa are elevated ( 16 ), indicating that chemokine induction is important for efforts to improve vaccine efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…76 The addition of CCL20 resulted in significant increases in IgA and IgG titers and a subsequent increase in nasopharyngeal clearance of NTHi. The same group tested the efficacy of fms-like tyrosine kinase receptor 3 ligand as a mucosal adjuvant with P6 protein.…”
Section: Progress In Identification Of New Vaccine Candidatesmentioning
confidence: 99%
“…In comparison with MIP-1β and MCP-1, mucosal genetic co-transfer of MIP-2 or MIP-1α with genetic antigen rendered recipients (mice) more resistant to HSV intravaginal infection. Nasal application of MIP-3α with P6 protein of nontypable Haemophilus influenzae (NTHi) induced an increase in the number of dendritic cells in murine NALT and P6-specific nasal wash IgA and serum IgG titers (Kodama et al, 2011 ). Accordingly, the clearance of NTHi was enhanced in MIP-3α immunized group.…”
Section: Mips and Mcpsmentioning
confidence: 99%